In vivo assay of p53 function in homologous recombination between simian virus 40 chromosomes. - Wiesmüller, L (1996)
To investigate a possible role of p53 in DNA exchange mechanisms, we have developed a model system which allows us to quantify homologous recombination rates in eukaryotic cells. We generated two types of simian virus 40 (SV40) whose genomes were mutated in such a way that upon double infection of monkey cells, virus particles can be released only after interchromosomal exchange of genetic material. This test system allowed us to determine recombination rates in the order of 10(-4) to 10(-6) for chromatin-associated SV40 genomes. To study the role of p53-T-antigen (T-Ag) complexes in this process, we designed viral test genomes with an additional mutation leading to a single amino acid exchange in T-Ag (D402H) and specifically blocking T-Ag-p53 interactions. Analysis of primary rhesus monkey cells endogenously expressing wild-type p53 showed a decreased recombination rate upon loss of efficient T-Ag-p53 complex formation. However, cells expressing mutant p53 (LLC-MK2 cells), the introduction of mutant T-Ag did not affect the DNA exchange rates. Our data are interpreted to indicate an inhibitory role of wild-type p53 in recombination. In agreement with this hypothesis, p53-T-Ag complex formation alleviates the inhibitory effect of wild-type p53.